Keaslian dan Keterpaduan dalam Pengelolaan Warisan Budaya Bawah Air (Studi Kasus Situs Arkelologi Bawah Air Moko, Bau-Bau) - Yadi Mulyadi (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
The problem of originality and unity in the contexts of cultural heritage preservation, principally in archaeological concept theory is very interesting to study, relation with cultural resource management. Cultural heritage preservation had to be accomplised that still follow the public condition, so that it can be a win-win solution. The necessary of originally and unity in cultural heritage preservation context, focused under water cultural heritage, especially with case study of the cave at Moko, Bau-bau